Gut microbiota: A new therapeutic target for diabetic cardiomyopathy - Yuan, Suxin; Cai, Zhengyao; Luan, Xingzhao; Wang, Haibo; Zhong, Yi; Deng, Li; Feng, Jian (Frontiers in Pharmacology, 2022)
Diabetic cardiomyopathy seriously affects quality of life and even threatens life safety of patients. The pathogenesis of diabetic cardiomyopathy is complex and multifactorial, and it is widely accepted that its mechanisms include oxidative stress, inflammation, insulin resistance, apoptosis, and autophagy. Some studies have shown that gut microbiota plays an important role in cardiovascular diseases. Gut microbiota and its metabolites can affect the development of diabetic cardiomyopathy by regulating oxidative stress, inflammation, insulin resistance, apoptosis, and autophagy. Here, the mechanisms of gut microbiota and its metabolites resulting in diabetic cardiomyopathy are reviewed. Gut microbiota may be a new therapeutic target for diabetic cardiomyopathy.